Upaya Meningkatkan Minat Belajar Peserta Didik pada Materi Pengukuran Berbantuan Virtual Laboratorium OLABS pada Fase E SMAS Islam Darunnajah Sumenep - Herman Jufri Andi; Analiatus Shofiyah; Siska Siska; Syaiful Bahri; Moh Syamsul (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This research targets to increase college students' interest in studying physics with the help of OLABS media or virtual, the technique used is school room action research (PTK). Which entails  cycles with  meeting periods in every cycle. The difficulty of this study is elegance X college students with a complete of 15 college students. The records series method turned into accomplished using questionnaires and observations. based totally at the research that has been carried out in the pre-cycle degree, the average percentage of students' hobby in mastering physics became obtained through 60%, the "low class" in the first cycle turned into obtained by way of the average percent of students' interest in getting to know physics of seventy five%, the "medium category" within the 2nd cycle become received by using the average percent of students' interest in gaining knowledge of physics of 89% "high category". This indicates an boom in college students' interest in mastering physics from pre-cycle to cycle I by means of 15% and an boom from cycle I to cycle II by means of 14%. based totally on the analysis of pre-cycle information, cycle I and cycle II received an average increase inside the typical percent of physics getting to know interest through 29% so that it may be concluded that through OLABS media or virtual practicum can boom students' hobby in studying physics.